2012
DOI: 10.7314/apjcp.2012.13.3.923
|View full text |Cite
|
Sign up to set email alerts
|

Early Efficacy of Endostar Combined with Chemoradiotherapy for Advanced Cervical Cancers

Abstract: Asian Pacific J Cancer Prev, 13, 923-926 IntroductionCervical cancer is the most common gynecologic cancer. Surgery or radiotherapy can achieve satisfactory effect for early stage cervical cancer, while in the late stage (II b-IV a period) the main treatment therapy is radiation. At present, many studies all over the world reported that radiotherapy combined with chemotherapy can improve the survival rate of patients with cervical cancer. Concurrent chemoradiation, using cisplatin-based chemotheraphy (either c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Endostar® can also inhibit human lung adenocarcinoma cell line SPC-A4. In addition, in in vitro experiments, results have showed that Endostar® can suppress the migration of HHEC,the formation of Tube, and the angiogenesis of Chorio Allantioc Membrane, and it can also suppress mouse tumor models (S180 sarcoma, H22 liver cancer ) and human xenograft tumor models (SPC-A4 lung adenocarcinoma, SGC7901 gastric cancer, HeLa cervical cancer, SMMC-7721 liver cancer and Bel7402 liver cancer) (Jia et al, 2012;Ke et al, 2012). In 2007, Endostar® became the first-line drug in the treatment of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Endostar® can also inhibit human lung adenocarcinoma cell line SPC-A4. In addition, in in vitro experiments, results have showed that Endostar® can suppress the migration of HHEC,the formation of Tube, and the angiogenesis of Chorio Allantioc Membrane, and it can also suppress mouse tumor models (S180 sarcoma, H22 liver cancer ) and human xenograft tumor models (SPC-A4 lung adenocarcinoma, SGC7901 gastric cancer, HeLa cervical cancer, SMMC-7721 liver cancer and Bel7402 liver cancer) (Jia et al, 2012;Ke et al, 2012). In 2007, Endostar® became the first-line drug in the treatment of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Endostar can suppress tumour growth in mouse models (S180 sarcoma, H22 liver cancer) and human xenograft models (SPC-A4 lung adenocarcinoma, SGC7901 gastric cancer, HeLa cervical cancer, SMMC-7721 and Bel7402 liver cancer). It has been reported that Endostar can suppress not only angiogenesis but also lymph node metastasis [16, 17]. The addition of Endostar results in significant improvement in response rate, median time to tumour progression, and clinical benefit rate in patients with advanced NSCLC [12, 18-20].…”
Section: Discussionmentioning
confidence: 99%
“…Endostar combining with chemoradiotherapy could improve the early outcome of the advanced cervical cancer, and adverse effects were not encountered (Ke et al, 2012). TC plus endostar seemed to improve ORR (39.3% vs. 23.0%) with a good safety profile in previous untreated advanced NSCLC, compared with TC alone (Han et al, 2011).…”
Section: Discussionmentioning
confidence: 95%